Existence and Nonexistence of Global Smooth Solutions for Damped p-system with "really Large" Initial Data (Journal of Partial Differential Equations, 1991)
In this paper, we extend the results in [4] to general p(v), and remove the condition (A) for existence, but keep it for nonexistence.
Keywords: quasilinear hyperbollc systems; global smooth solutions; existence and nonexistence